Concept of The Goals of Islamic Education Based on The Interpretation of Five Verses of The Qur'An - Nurdiana, Budi; Nasir, Tatang Muh; Gunawan, Ade Hendra; Syarif, Ahmad; Restiana, Dwi (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This research explores the concept of educational goals in Islam as derived from the interpretation of five key verses of the Qur’an. Education in the Qur’anic perspective aims to develop the holistic potential of human beings physical, spiritual, and intellectual so they can fulfill their role as servants of Allah (ʿabd) and His vicegerents (khalifah) on earth. The study employs a qualitative research design with a normative-juridical approach, emphasizing library research. Data sources include classical and contemporary tafsir works, scholarly articles, and educational literature. Data were collected through document analysis and processed using descriptive analysis techniques, which involve data reduction, categorization, and synthesis. The findings reveal that the Qur’an views education as a medium for cultivating intellectual capacity (ʿaql), elevating moral and social status through knowledge, and achieving ultimate well-being in both the worldly and spiritual realms. The five examined verses highlight essential objectives: servitude to Allah, fulfilling the responsibility as khalifah, nurturing critical thinking, advancing knowledge, and seeking divine pleasure. This study concludes that Islamic education must integrate these Qur’anic values to form holistic, ethical, and balanced individuals capable of contributing positively to society.